Fully-automated strength, agility and endurance tests assessment: an integrated low cost approach based on an instrumented chair - Gonçalves, José (2017)
In this paper it is described the prototyping of an instrumented chair that allows to fully-automate the ``Timed Up and Go'', the ``30-Second Chair Stand'' and the ``Hand-Force '' tests assessment. The presented functional chair prototype is a low cost approach that uses inexpensive sensors and the Arduino platform as the data acquisition board, with its software developed in LabVIEW. The ``Timed up and go test'' consists in measuring the time spent in the task execution of standing up from a chair, walk three meters with a maximum speed without running, turn a cone and going back to the initial position. The ``30-Second Chair Stand'' test consists in counting the number of completed chair stands in 30 seconds. It are agility, strength and endurance tests easy to setup and execute although they lack of repeatability, whenever the measures are taken manually, due to the rough errors that are introduced. The ``Hand-Force'' test consists in measuring the hand strength, the relevant data are the peak and average values of several tests. The referred data is important in order to evaluate hand rehabilitation treatment results.